Piezoelectric-driven self-biased very-low-frequency mechanical transmitting antenna and preparation method thereof

By filling the adhesive layer between the piezoelectric fiber composite material and the magnetostrictive phase with high elastic modulus and high residual magnetization, the internal magnetic gradient structure is formed, and the existing low-frequency magnetoelectric antennas are solved in the bandwidth and The limitations of cross-difference transmission capabilities have achieved miniaturization of self-biased very low-frequency mechanical transmitting antennas and efficient magnetic emission.

CN119447765AActive Publication Date: 2025-02-14WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411576901.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Existing low-frequency magnetoelectric antennas have limitations in bandwidth and cross-difference transmission capabilities, and the external biased magnetic field will cause additional noise sources and stress transmission problems, making it difficult to achieve miniaturization and efficient magnetic emission.

Method used

By filling the adhesive layer between the piezoelectric fiber composite material and the magnetostrictive phase with high elastic modulus and high residual magnetization, an internal magnetic gradient structure is formed to achieve a self-biasing effect and pass piezoelectric resonance through piezoelectric resonance Drive improves stress transmission efficiency.

Benefits of technology

The self-biased very low-frequency mechanical transmitting antenna is miniaturized, which improves the magnetic emission intensity and stress transmission efficiency under zero-biased conditions, meets the needs of low-frequency communication, and reduces additional noise sources and electromagnetic interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447765A_ABST
    Figure CN119447765A_ABST
Patent Text Reader

Abstract

The invention provides a self-biased very-low-frequency mechanical transmitting antenna driven by piezoelectricity and a preparation method of the self-biased very-low-frequency mechanical transmitting antenna. The preparation method comprises the following steps: step 1, preparing a piezoelectric ceramic material; step 2, cutting and slotting; thirdly, resin is poured; step 4, cutting the layer sheets; step 5, packaging; step 6, polarization treatment; step 7, preparing a bonding layer; and 8, hot-pressing and compounding. Compared with an existing magnetoelectric antenna, the self-biased very-low-frequency mechanical transmitting antenna has the advantages of being self-biased, high in piezoelectric property, miniaturized, free of extra noise sources and electromagnetic interference and the like, has the advantages of being high in stress transmission efficiency, small in ohmic loss and the like, can meet the requirement for miniaturization of the magnetoelectric mechanical antenna, is easy to form a large-scale array, and is suitable for large-scale popularization and application. The magnetic emission performance under zero bias is improved, and the low-frequency communication effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic communication, and in particular to a piezoelectric driven self-biased very low frequency mechanical transmitting antenna and a preparation method thereof. Background Art

[0002] With the rapid popularization of low-power electronic devices and smart sensor devices, the demand for miniaturized antennas in the field of medical devices has surged. Among them, low-frequency magnetoelectric antennas play a vital role in implantable medical device applications because they can provide miniaturized size, lower path loss and higher efficiency, thereby achieving therapeutic drugs, neural stimulation, and deep human body communication. However, these antennas have limitations in bandwidth and cross-medium transmission capabilities, and a bias magnetic field needs to be applied to achieve optimal magnetic emission performance. This is mainly because the introduction of a bias magnetic field will cause the magnetostrictive material to be in an easy magnetization state, thereby improving its stress-magnetization response behavior. In existing studies, a pair of permanent magnets or a Helmholtz coil carrying direct current is usually used to provide the required bias magnetic field (H bias ), and the presence of permanent magnets or coils will lead to a larger size of the magneto-electromechanical antenna system, additional noise sources and electromagnetic interference, which are difficult to meet the needs of miniaturization of magneto-electromechanical antennas. Therefore, a novel design is needed to achieve efficient magnetic transmission without a DC magnetic field.

[0003] At present, there are two solutions to the problem of magnetic bias of low-frequency magnetoelectric antennas. One is to enhance the magnetic emission intensity under zero bias, and the other is to change the way the magnetic bias is applied. The ultimate goal is to improve the magnetization state of the magnetoelectric composite material under zero bias. However, the intervention of the entire magnetic layer in the sample will affect its stress transfer efficiency. Regarding the stress transfer problem of magnetoelectric composite materials, Hwang et al. (Enhancement of Magnetoelectric Conversion Achieved by Optimization of Interfacial Adhesion Layer in Laminate Composites [J]. ACS Appl. Mater. Interfaces, 2018, 10 (38): 32323-32330) proved through theoretical simulation that the thickness and elastic modulus of the adhesive layer will significantly affect the stress transfer efficiency. However, it is very difficult to directly increase the elastic modulus of the bonding layer. The cross-linking structure and degree of polymerization inside the adhesive will affect the elastic modulus of the bonding layer.

[0004] Therefore, it is urgent to develop a self-biased very low frequency mechanical transmitting antenna to solve the problems of additional noise sources and stress transfer caused by the external bias magnetic field, realize the enhancement of magnetic emission intensity under zero bias, and achieve low-frequency communication effect. Summary of the invention

[0005] In view of this, the present invention proposes a self-biased, high-piezoelectric, miniaturized, piezoelectrically driven self-biased very low frequency mechanical transmitting antenna without additional noise sources and electromagnetic interference, and a preparation method thereof. The self-biased very low frequency mechanical transmitting antenna has high stress transfer efficiency and low ohmic loss, can meet the needs of miniaturization of magneto-electromechanical antennas, is easy to form an array on a large scale, improves the magnetic transmission performance under zero bias conditions, and achieves low-frequency communication effects.

[0006] In a first aspect, the present invention provides a method for preparing a piezoelectric driven self-biased very low frequency mechanical transmitting antenna, comprising the following steps:

[0007] Step 1: Preparation of piezoelectric ceramic materials

[0008] The raw materials are prepared and mixed, and the piezoelectric ceramic material is obtained after pre-sintering, granulation, molding, debinding and sintering;

[0009] Step 2: Cutting and Slotting

[0010] Cutting and grooving the piezoelectric fiber composite material prepared in step 1;

[0011] Step 3: Pouring resin

[0012] pouring resin into the grooved piezoelectric fiber composite material in step 2, and cooling;

[0013] Step 4: Cut the layers

[0014] Slicing the product after cooling in step 3 to obtain a piezoelectric fiber sheet;

[0015] Step 5: Packaging

[0016] Using an adhesive to bond the piezoelectric fiber sheet of step 4 to the interdigital electrodes, and hot pressing to obtain a piezoelectric fiber composite material;

[0017] Step 6: Polarization

[0018] Performing a polarization treatment on the piezoelectric fiber composite material of step five;

[0019] Step 7: Prepare the bonding layer

[0020] Adhesives filled with magnetic particles;

[0021] Step 8: Hot pressing composite

[0022] The piezoelectric fiber composite material polarized in step six is ​​hot-pressed and composited with the magnetostrictive phase by using an adhesive layer to obtain a self-biased very low frequency mechanical transmitting antenna.

[0023] By adopting the above technical solution, the present invention fills magnetic particles in the bonding layer between the piezoelectric fiber composite material (MFC) and the magnetostrictive phase (Metglas), and the magnetic particles with high elastic modulus and high residual magnetization provide advantageous conditions for the stress state and magnetization state of the magnetostrictive phase. Since the difference in magnetic properties between the magnetic particles and the magnetostrictive phase in the bonding layer will cause an internal magnetic field, the magneto-electro-mechanical antenna with a magnetic gradient structure can achieve self-biasing, and at the same time, the high elastic modulus and small thickness of the bonding layer can improve the stress transfer of the strain layer (i.e., the interface between the piezoelectric phase and the magneto-strictive phase). Thereby, the magnetic emission intensity of the magneto-electro-mechanical antenna under zero bias conditions is improved, and the very low frequency communication effect is achieved.

[0024] On the basis of the above technical scheme, preferably, in step one, the preparation of the piezoelectric ceramic material comprises the following steps: ball milling the ceramic powder, adding a 5% by mass polyvinyl alcohol solution, grinding and granulating, pressing and molding, debinding, and sintering to obtain the piezoelectric ceramic material.

[0025] On the basis of the above technical solution, preferably, the mass ratio of the ceramic powder to the polyvinyl alcohol solution is 10-15:1.

[0026] More preferably, the mass ratio of the ceramic powder to the polyvinyl alcohol solution is 15:1.

[0027] In the present invention, the selection of ceramic powder raw materials includes but is not limited to: lead zirconate titanate niobate ceramic blocks, polyvinylidene fluoride ceramic blocks or lead zirconate titanate ceramic blocks; the present invention preferably uses lead zirconate titanate ceramic blocks, which have a particle size of less than 0.12 mm after crushing.

[0028] On the basis of the above technical solution, preferably, the preparation of the piezoelectric ceramic material comprises the following steps: placing zirconate titanate ceramic powder in a crucible for compaction and mixing, and then placing it in a muffle furnace for pre-sintering, and cooling it with the furnace to obtain a pre-sintered sample. Thereafter, ball milling is performed, polyvinyl alcohol solution is added, grinding and granulation is performed, pressure molding is performed, binder is removed, and sintering is performed to obtain a piezoelectric ceramic material.

[0029] More preferably, the ball milling medium includes but is not limited to alcohol, the rotation speed is 200-300 r / min, and the time is 10-20 h.

[0030] More preferably, the grinding requirement is until the powder becomes uniform particles and is not easy to stick to the wall, and the particle size does not exceed 100 mesh.

[0031] More preferably, the pressing conditions are: cold isostatic pressing under vacuum conditions, and all-round pressure is required.

[0032] More preferably, the green body needs to be buried with powder before sintering, that is, a layer of powder remaining after molding is spread around the green body to avoid lead loss.

[0033] Based on the above technical solution, preferably, in step 2, the groove depth is about 4 / 5 of the ceramic material.

[0034] On the basis of the above technical solution, preferably, the casting resin specifically includes: ultrasonic cleaning the product in step 2, adding adhesive under vacuum, exhausting, and cooling.

[0035] In the present invention, the elastic modulus of the adhesive is greater than 3 GPa, and specific choices thereof include but are not limited to epoxy resin, acrylate, silicone, rubber or other flexible insulating materials; epoxy resin is preferred in the present invention.

[0036] More preferably, before pouring the resin, the epoxy resin glue needs to be placed in a 60° C. drying oven for 15 minutes to increase its fluidity.

[0037] More preferably, the amount of epoxy resin added is positively correlated to the volume of the ceramic block, and its volume percentage is 30%.

[0038] On the basis of the above technical solution, preferably, in step 4, the sheet layer is generally 0.3 mm thick, 10 cm long and 2 cm wide.

[0039] On the basis of the above technical solution, preferably, the amount of the adhesive is about 0.5-1.0 g, so that the adhesive can be evenly coated on the piezoelectric fiber sheet.

[0040] On the basis of the above technical solution, preferably, the polarization condition is 1.5 to 3.5 kV / mm.

[0041] On the basis of the above technical solution, preferably, the use of magnetic particles to fill the adhesive layer specifically includes:

[0042] The magnetic particles with a volume fraction of 10 to 50% are added into the epoxy resin, stirred under heating conditions, an amine curing agent is added, and ultrasonic treatment is performed to obtain an adhesive layer.

[0043] In the present invention, the magnetic particles are selected from materials with an elastic modulus of 10GPa to 100Gpa, a residual magnetization of 10 to 200emu / g, and a particle size of 1 to 5μm. The selection of magnetic particles of the present invention includes but is not limited to Terfenol-D powder or cobalt ferrite particles. Terfenol-D powder is preferred in the present invention.

[0044] By adopting the above technical solution, the addition of Terfenol-D powder in the adhesive layer and the setting of its volume fraction can adjust the internal bias magnetic field size of the mechanical antenna and the elastic modulus of the epoxy adhesive layer. For Terfenol-D powder, if the particle size is too large, it is not easy to fill and will affect the interface bonding. If the particle size is too small, it will agglomerate and be difficult to disperse. Therefore, its particle size is controlled to 1 to 5 μm. In addition, when the volume fraction of Terfenol-D powder is less than 10%, the magnetic emission intensity under zero bias is very weak; when the volume fraction of Terfenol-D powder exceeds 50%, it may cause uneven dispersion of filler and poor interface bonding quality, resulting in a decrease in its performance.

[0045] In the present invention, the elastic modulus of the adhesive layer filled with Terfenol-D powder is 3 GPa to 10 GPa, and the thickness is 0.15 to 0.4 μm.

[0046] By adopting the above technical solution, the magnetic emission effect of the adhesive layer with a low elastic modulus will be reduced, and the adhesive layer with this thickness will have a better stress transfer effect and better magnetic emission performance.

[0047] On the basis of the above technical solution, preferably, the conditions of the hot pressing composite are set as: pressure 2-20 MPa, temperature 50-100° C., and curing time 5-30 min.

[0048] By adopting the above technical solution, the interface bonding state of the composite material and the cross-linking curing degree of the adhesive can be significantly improved, thereby affecting the stress transfer and magnetic emission properties of the magnetoelectric composite material.

[0049] In a second aspect, the present invention relates to a piezoelectrically driven self-biased very low frequency mechanical transmitting antenna prepared by the above method, wherein the self-biased very low frequency mechanical transmitting antenna comprises, from the inside to the outside, a piezoelectric phase, an adhesive layer and a magnetostrictive phase; the piezoelectric phase and the magnetostrictive phase are connected through the adhesive layer.

[0050] On the basis of the above technical solution, preferably, the material selection of the magnetostrictive phase includes but is not limited to magnetic amorphous alloys, and the magnetostrictive phase of the present invention is preferably Metglas.

[0051] On the basis of the above technical solution, preferably, two holes are opened on one side of the piezoelectric phase, and the two holes are used for externally connecting wires to apply an external DC electric field.

[0052] By adopting the above technical solution, the piezoelectric phase is used as the excitation source, and the external wire generates resonance through the inverse piezoelectric effect to drive the ferromagnetic material to vibrate, which can convert electrical energy into mechanical energy and then into magnetic field energy.

[0053] The self-biased very low frequency mechanical transmitting antenna provided by the present invention has the following beneficial effects compared with the prior art:

[0054] (1) Compared with the existing magneto-electromechanical antenna, the self-biased very low frequency mechanical transmitting antenna of the present invention has the characteristics of self-bias, high piezoelectricity, miniaturization, no additional noise source and electromagnetic interference, and has the advantages of high stress transfer efficiency and low ohmic loss. It can meet the needs of miniaturization of magneto-electromechanical antennas, is easy to form an array on a large scale, improves the magnetic transmission performance under zero bias, and achieves low-frequency communication effects.

[0055] (2) The self-biased very low frequency mechanical transmitting antenna of the present invention can obtain an internal magnetic gradient structure by introducing magnetic particles into the adhesive layer, thereby bringing about a self-biasing effect and solving the problem of additional noise sources and electromagnetic interference caused by an external bias magnetic field.

[0056] (3) The self-biased very low frequency mechanical transmitting antenna of the present invention uses an epoxy adhesive layer with a high elastic modulus, which can enhance the stress transfer between the piezoelectric phase and the magnetostrictive phase, thereby solving the problem that the thickness and elastic modulus of the adhesive layer will significantly affect the stress transfer efficiency.

[0057] (4) The self-biased very low frequency mechanical transmitting antenna of the present invention is driven by piezoelectric resonance, and has the characteristics of small ohmic loss and high efficiency. It can meet the needs of miniaturization of magneto-electromechanical antennas, is easy to form an array on a large scale, improves magnetic transmission performance, and achieves low-frequency communication effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0059] Figure 1 The process flow chart of preparing the self-biased very low frequency mechanical transmitting antenna of the present invention;

[0060] Figure 2 A structural diagram of a self-biased very low frequency mechanical transmitting antenna prepared by the present invention;

[0061] Figure 3 Magnetic emission intensity diagrams of M-0, M-1, M-2, and M-3 under zero bias in various embodiments of the present invention;

[0062] Figure 4 Graphs showing changes in magnetic emission intensity of M-0, M-1, M-2, and M-3 with voltage under zero bias in various embodiments of the present invention;

[0063] Figure 5Graph showing the variation of magnetic emission intensity with frequency in Examples M-0 and M-3 of the present invention;

[0064] Figure 6 This is a comparison diagram of the change of magnetic emission intensity with magnetic field direction under zero bias in embodiments M-0 and M-3 of the present invention;

[0065] Figure 7 This is a signal modulation diagram of Example M-3 of the present invention. DETAILED DESCRIPTION

[0066] The inventors have found in practice that existing magneto-electromechanical antennas generally have the following problems:

[0067] (1) The existence of existing permanent magnets or coils will lead to problems such as larger size of the magneto-electromechanical antenna system, additional noise sources and electromagnetic interference, which are difficult to meet the needs of miniaturization of magneto-electromechanical antennas.

[0068] (2) From the perspective of stress transfer, the low elastic modulus adhesive layer of the magnetoelectric composite material will affect its magnetic emission performance.

[0069] (3) Low-frequency magnetoelectric antennas have limitations in bandwidth and cross-medium transmission capabilities.

[0070] In order to solve the above technical problems, the inventors made the present invention through further research.

[0071] The present invention prepares a self-biased very low frequency mechanical transmitting antenna, which provides advantageous conditions for the stress state and magnetization state of the magnetostrictive phase by filling the bonding layer between the piezoelectric fiber composite material (MFC) and the magnetostrictive phase (Metglas) with magnetic particles with high elastic modulus and high residual magnetization. In addition, due to the difference in magnetic properties between the magnetic particles and the magnetostrictive phase in the bonding layer, an internal magnetic field is caused, a magnetic gradient structure is generated, and then a self-bias phenomenon can be achieved. At the same time, a high elastic modulus and a small bonding layer thickness can improve the stress transfer between the piezoelectric phase and the magnetostrictive phase, thereby improving the magnetic emission intensity of the magnetoelectric mechanical antenna under zero bias conditions and achieving a very low frequency communication effect.

[0072] Refer to the attached Figure 1 As shown, the process flow of preparing the self-biased very low frequency mechanical transmitting antenna of the present invention specifically includes the following steps:

[0073] Step 1: Preparation of piezoelectric ceramic materials

[0074] The raw materials are prepared and mixed, and the piezoelectric ceramic material is obtained after pre-sintering, granulation, molding, debinding and sintering;

[0075] Step 2: Cutting and Slotting

[0076] Cutting and grooving the piezoelectric fiber composite material prepared in step 1;

[0077] Step 3: Pouring resin

[0078] pouring resin into the grooved piezoelectric fiber composite material in step 2, and cooling;

[0079] Step 4: Cut the layers

[0080] Slicing the product after cooling in step 3 to obtain a piezoelectric fiber sheet;

[0081] Step 5: Packaging

[0082] Using an adhesive to bond the piezoelectric fiber sheet of step 4 to the interdigital electrodes, and hot pressing to obtain a piezoelectric fiber composite material;

[0083] Step 6: Polarization

[0084] Performing a polarization treatment on the piezoelectric fiber composite material of step five;

[0085] Step 7: Prepare the bonding layer

[0086] Using magnetic particles to fill the bonding layer;

[0087] Step 8: Hot pressing composite

[0088] The piezoelectric fiber composite material polarized in step 6 is hot-pressed with the magnetostrictive phase by using the adhesive layer to obtain a self-biased very low frequency mechanical transmitting antenna. The structure is shown in the attached figure. Figure 2 shown.

[0089] In the present invention, the preparation of the piezoelectric fiber composite material (MFC), that is, the specific operations of steps one to five are prepared with reference to a piezoelectric fiber composite structure layer disclosed in Chinese patent CN201510907240.4, and the relevant contents of the present invention are only summarized.

[0090] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0091] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of materials mainly involved in the examples are all conventional commercial products unless otherwise specified.

[0092] Example 1

[0093] This embodiment provides a method for preparing a very low frequency mechanical transmitting antenna, comprising the following steps:

[0094] The lead zirconate titanate (PZT) powder is fully mixed and pre-fired by ball milling and sieving technology. The pre-fired block is broken into pieces and placed in a ball mill. A 5wt% polyvinyl alcohol (PVA) solution is added to the dried particles and ground until the powder becomes uniform and not easy to hang on the wall. After passing through a 100-mesh sieve, a ceramic powder is obtained. Then, the lead zirconate titanate piezoelectric ceramic powder is flattened and further air bubbles are discharged by hot pressing technology, and then the lead zirconate titanate piezoelectric ceramic block is obtained by debinding and high-temperature sintering. After cleaning and drying, it is cut by a cutting machine to obtain a piezoelectric fiber array (fiber length 100mm, width 0.6mm, spacing 0.3mm). Epoxy resin is poured into it, and the layer slices (length 100mm, width 20mm, thickness 0.3mm) are cut after the block is completely solidified. Two mirror-symmetrical interdigital electrodes are taken out for packaging. The polarization conditions of the piezoelectric phase are 3kV / mm and 80℃ oil bath. After completion, the required MFC is obtained.

[0095] The Metglas film was cut into sheets with a length of 100 mm and a width of 20 mm. An amine curing agent (Westsystem 206) was added to the epoxy resin (West system 105), stirred for a period of time under heating conditions to reduce the viscosity, and then ultrasonically treated for 10 minutes. The epoxy resin was scraped onto the MFC and Metglas with a blade to bond the two. Finally, the Metglas / MFC laminate was compacted in a hot press at a pressure of 2 MPa and cured at 60°C for 15 minutes to obtain a magneto-electromechanical antenna, which was recorded as M-0.

[0096] Example 2

[0097] This embodiment provides a method for preparing a self-biased magneto-electromechanical antenna, the steps of which are as follows:

[0098] The lead zirconate titanate (PZT) powder is fully mixed and pre-fired by ball milling and sieving technology. The pre-fired block is broken into pieces and placed in a ball mill. A 5wt% polyvinyl alcohol (PVA) solution is added to the dried particles and ground until the powder becomes uniform and not easy to hang on the wall. After passing through a 100-mesh sieve, a ceramic powder is obtained. Then, the lead zirconate titanate piezoelectric ceramic powder is flattened and further air bubbles are discharged by hot pressing technology, and then the lead zirconate titanate piezoelectric ceramic block is obtained by debinding and high-temperature sintering. After cleaning and drying, it is cut by a cutting machine to obtain a piezoelectric fiber array (fiber length 100mm, width 0.6mm, spacing 0.3mm). Epoxy resin is poured into it, and the layer slices (length 100mm, width 20mm, thickness 0.3mm) are cut after the block is completely solidified. Two mirror-symmetrical interdigital electrodes are taken out for packaging. The polarization conditions of the piezoelectric phase are 3kV / mm and 80℃ oil bath. After completion, the required MFC is obtained.

[0099] Metglas film was cut into sheets with a length of 100 mm and a width of 20 mm. Terfenol-D powder was added to epoxy resin (West system 105) to form a 10 vol% Terfenol-D / epoxy resin mixture, which was stirred under heating conditions for a period of time to reduce the viscosity and promote the dispersion of Terfenol-D powder in the epoxy resin. An amine curing agent (West system 206) was then added, and ultrasonic treatment was performed for 10 min. The 10 vol% Terfenol-D / epoxy resin mixture was scraped onto MFC and Metglas with a blade to bond the two. Finally, the Metglas / MFC laminate was compacted in a hot press at a pressure of 2 MPa and cured at 60°C for 15 min to obtain a self-biased magneto-electromechanical antenna, denoted as M-1.

[0100] Example 3

[0101] This embodiment provides a method for preparing a self-biased magneto-electromechanical antenna, the steps of which are as follows:

[0102] The lead zirconate titanate (PZT) powder is fully mixed and pre-fired by ball milling and sieving technology. The pre-fired block is broken into pieces and placed in a ball mill. A 5wt% polyvinyl alcohol (PVA) solution is added to the dried particles and ground until the powder becomes uniform and not easy to hang on the wall. After passing through a 100-mesh sieve, a ceramic powder is obtained. Then, the lead zirconate titanate piezoelectric ceramic powder is flattened and further air bubbles are discharged by hot pressing technology, and then the lead zirconate titanate piezoelectric ceramic block is obtained by debinding and high-temperature sintering. After cleaning and drying, it is cut by a cutting machine to obtain a piezoelectric fiber array (fiber length 100mm, width 0.6mm, spacing 0.3mm). Epoxy resin is poured into it, and the layer slices (length 100mm, width 20mm, thickness 0.3mm) are cut after the block is completely solidified. Two mirror-symmetrical interdigital electrodes are taken out for packaging. The polarization conditions of the piezoelectric phase are 3kV / mm and 80℃ oil bath. After completion, the required MFC is obtained.

[0103] Metglas film was cut into sheets with a length of 100 mm and a width of 20 mm. Terfenol-D powder was added to epoxy resin (West system 105) to form a 30 vol% Terfenol-D / epoxy resin mixture, which was stirred under heating conditions for a period of time to reduce the viscosity and promote the dispersion of Terfenol-D powder in the epoxy resin. An amine curing agent (West system 206) was then added, and ultrasonic treatment was performed for 10 minutes. The 30 vol% Terfenol-D / epoxy resin mixture was scraped onto MFC and Metglas with a blade to bond the two. Finally, the Metglas / MFC laminate was compacted in a hot press at a pressure of 4 MPa and cured at 70°C for 20 minutes to obtain a self-biased magneto-electromechanical antenna, which was recorded as M-2.

[0104] Example 4

[0105] This embodiment provides a method for preparing a self-biased magneto-electromechanical antenna, the steps of which are as follows:

[0106] The lead zirconate titanate (PZT) powder is fully mixed and pre-fired by ball milling and sieving technology. The pre-fired block is broken into pieces and placed in a ball mill. A 5wt% polyvinyl alcohol (PVA) solution is added to the dried particles and ground until the powder becomes uniform and not easy to hang on the wall. After passing through a 100-mesh sieve, a ceramic powder is obtained. Then, the lead zirconate titanate piezoelectric ceramic powder is flattened and further air bubbles are discharged by hot pressing technology, and then the lead zirconate titanate piezoelectric ceramic block is obtained by debinding and high-temperature sintering. After cleaning and drying, it is cut by a cutting machine to obtain a piezoelectric fiber array (fiber length 100mm, width 0.6mm, spacing 0.3mm). Epoxy resin is poured into it, and the layer slices (length 100mm, width 20mm, thickness 0.3mm) are cut after the block is completely solidified. Two mirror-symmetrical interdigital electrodes are taken out for packaging. The polarization conditions of the piezoelectric phase are 3kV / mm and 80℃ oil bath. After completion, the required MFC is obtained.

[0107] Metglas film was cut into sheets with a length of 100 mm and a width of 20 mm. A certain amount of Terfenol-D powder was added to epoxy resin (West system 105) to form a 50 vol% Terfenol-D / epoxy resin mixture, which was stirred under heating conditions for a period of time to reduce the viscosity and promote the dispersion of Terfenol-D powder in the epoxy resin. Then, an amine curing agent (West system 206) was added, and ultrasonic treatment was performed for 10 minutes. The 50 vol% Terfenol-D / epoxy resin mixture was scraped onto MFC and Metglas with a blade to bond the two. Finally, the Metglas / MFC laminate was compacted in a hot press at a pressure of 8 MPa and cured at 80°C for 25 minutes to obtain a self-biased magneto-electromechanical antenna, which was recorded as M-3.

[0108] The magnetic emission performance of the above-mentioned embodiments 1 to 4 is tested, with specific reference to the literature (Magneto-Mechano-Electric Antenna for Portable VLF Transmission[J]. Adv. Elect. Mater, 2023, 9(7): 2300096), including: using a phase-locked amplifier (SR830, Stanford Research Systems, USA) to measure the magnetic emission intensity of the magneto-electric composite material as a function of frequency under an unbiased magnetic field, and testing the change of the magnetic emission intensity with voltage. In this part, a homemade coil is used as a long-distance receiver to capture the radiation signals in all directions of the magnetic field.

[0109] By performing digital data transmission detection on the above-mentioned embodiments 1 to 4, specifically referring to the literature (Bias-free Very Low Frequency Magnetoelectric Antenna [J]. Appl. Phys. Lett, 2023, 122 (26): 262901), including: using a function generator to convert a binary bit stream into an ASK signal, and then amplifying it through a power amplifier. Using a loop antenna to measure the magnetic radiation signal and demodulating it through a computer.

[0110] Test results such as Figure 3 to Figure 7 shown.

[0111] Depend on Figure 3 It can be seen that compared with M-0, the M-1, M-2, and M-3 samples with magnetic gradient structures have better magnetic emission performance under zero bias, among which the magnetic emission intensity of M-3 is the best, which is 2.8 times that of M-0. This is due to the fact that the appropriate amount of magnetic particles provides a better internal magnetic field and interface combination, which facilitates the realization of the self-bias effect.

[0112] Depend on Figure 4 It can be seen that compared with M-0, the M-1, M-2, and M-3 samples with magnetic gradient structures have greater power output at the same voltage at zero bias, among which M-3 has the best output.

[0113] Depend on Figure 5 It can be seen that M-0 and M-3 have the best magnetic emission intensity near 13kHz, which can meet the very low frequency communication range, and M-3 has a greater magnetic emission intensity.

[0114] Depend on Figure 6 It can be seen that when receiving signals with a coil at 40cm, it can be seen that the radiation intensity of M-0 and M-3 is the largest at 0° and 180°, and M-3 has better directivity.

[0115] Depend on Figure 7 It can be seen that for digital signal transmission of M-3, it can be seen that the 1Hz binary bit stream is converted into an ASK modulated signal and loaded at the resonant frequency of the antenna. After demodulation and low-pass filtering, the measured signal is successfully converted into the original bit stream without distortion, thus achieving very low frequency communication.

[0116] In summary, the self-biased magneto-electromechanical antenna with a magnetic gradient structure prepared by the present invention not only performs well in terms of magnetic emission intensity and power output, but also shows significant advantages in the application of very low frequency communication. This provides an important theoretical basis and technical support for the development of new magneto-electromechanical composite materials and their applications in the fields of wireless communication.

[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a piezoelectric driven self-biased very low frequency mechanical transmitting antenna, characterized in that: The method comprises the following steps: Step 1: Preparation of piezoelectric ceramic materials The raw materials are prepared and mixed, and the piezoelectric ceramic material is obtained after pre-sintering, granulation, molding, debinding and sintering; Step 2: Cutting and Slotting Cutting and grooving the piezoelectric fiber composite material prepared in step 1; Step 3: Pouring resin pouring resin into the grooved piezoelectric fiber composite material in step 2, and cooling; Step 4: Cut the layers Slicing the product after cooling in step 3 to obtain a piezoelectric fiber sheet; Step 5: Packaging Using an adhesive to bond the piezoelectric fiber sheet of step 4 to the interdigital electrodes, and hot pressing to obtain a piezoelectric fiber composite material; Step 6: Polarization Performing a polarization treatment on the piezoelectric fiber composite material of step five; Step 7: Prepare the bonding layer Adhesives filled with magnetic particles; Step 8: Hot pressing composite The piezoelectric fiber composite material polarized in step six is ​​hot-pressed and composited with the magnetostrictive phase by using an adhesive layer to obtain a self-biased very low frequency mechanical transmitting antenna.

2. The preparation method according to claim 1, characterized in that In step 1, the preparation of the piezoelectric ceramic material includes the following steps: ball milling the ceramic powder, adding a polyvinyl alcohol solution with a mass fraction of 5%, grinding and granulating, pressing and molding, debinding, and sintering to obtain the piezoelectric ceramic material.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the ceramic powder to the polyvinyl alcohol solution is 10 to 15:

1.

4. The preparation method according to claim 1, characterized in that: In step three, the pouring of resin specifically includes: ultrasonic cleaning of the product in step two, adding adhesive under vacuum, exhausting, and cooling; the elastic modulus of the adhesive is greater than 3 GPa.

5. The preparation method according to claim 1, characterized in that: In step six, the polarization condition is 1.5 to 3.5 kV / mm.

6. The preparation method according to claim 1, characterized in that: In step seven, the step of filling the adhesive layer with magnetic particles specifically includes: Adding 10-50% volume fraction of magnetic particles into the adhesive, stirring under heating conditions, adding an amine curing agent, and ultrasonically treating to obtain an adhesive layer; The elastic modulus of the magnetic particles is 10 GPa to 100 GPa, the residual magnetization intensity is 10 to 200 emu / g, and the particle size is 1 to 5 μm.

7. The preparation method according to claim 1, characterized in that: In step eight, the conditions for the hot pressing composite are set as: pressure 2-20 MPa, temperature 50-100° C., and curing time 5-30 min.

8. A piezoelectric driven self-biased very low frequency mechanical transmitting antenna, characterized in that: The self-biased very low frequency mechanical transmitting antenna is prepared by the preparation method described in any one of claims 1 to 7.

9. The piezoelectric driven self-biased very low frequency mechanical transmitting antenna according to claim 8, characterized in that: The self-biased very low frequency mechanical transmitting antenna comprises, from inside to outside, a piezoelectric phase, an adhesive layer and a magnetostrictive phase; the piezoelectric phase and the magnetostrictive phase are connected through the adhesive layer.

10. The piezoelectric driven self-biased very low frequency mechanical transmitting antenna according to claim 9, characterized in that: Two holes are opened on one side of the piezoelectric phase, and the two holes are used for externally connecting electric wires to apply an external direct current electric field.

Citation Information

Patent Citations

  • Method for preparing piezoelectric fiber composite structural layer

    CN105405964A

  • A method for preparing large-size thick-film piezoelectric composite materials by casting

    CN102299254A

  • Axial continuous shearing strain piezoelectric fiber composite material and preparation method thereof

    CN112563406A

  • Flexible magnetoelectric composite low-frequency mechanical antenna and preparation method thereof

    CN114597638A

Cited By

  • Dual-drive very-low-frequency mechanical antenna system and communication control method thereof

    CN122247477A